HISTOPATHOLOGICAL AND BIOCHEMICAL EFFECTS OF CHRONIC PROPOFOL EXPOSURE ON DOGS - Ahmed Ali Hussein; Jihad A. Ahmed (Basrah Journal of Veterinary Research)
This study was conducted in the veterinary medical college, university of Basra.The objective of this study was to know the histopathological effect of propofol asanesthetic agent on dogs organs (central nervous system, heart, liver) and effect ofpropofol on liver enzymes, Propofol administration for 90 days by intravenous (intocephalic vein) into 8 adult dogs which divided into two equal groups. The controlgroup was injected with 0.9% normal saline (1ml/kg), while the propofol group wasinjected with (10mg /kg) body weight of dog per day. The measured parameters AST,ALT showed a significant difference in groups between zero time and after 90 days.Also the histopathological result of brain, heart and liver showed significant changesas atrophic neurons, nerve fibers vacuolation and gliosis and histopathological resultof heart section showed white areas of degenerate myocardial muscle cells withpresence of adipose tissue and congested blood vessels, white areas of degeneratemyocyte as infiltration of adipose tissue at pericardial region (periphery) and areas ofdestruction of myocardial muscle cells while the histopathological changes ofhepatocyte showed septal fibrosis, bile duct proliferation, fine defuse vacuolation ofhepatocyte and hypertrophic of bile duct. The uses of propofol for the long term maycause serious Histopathological injuries in many organs particularly the brain andliver that may due to its direct interaction in these structural units.